2007
DOI: 10.1007/s11740-007-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface reconstruction for incremental forming

Abstract: In spite of extensive efforts being made with regard to virtual process optimization technology, the production of prototype parts is still a necessity. With respect to the production of sheet metal parts in low quantities, incremental sheet metal forming (ISMF) is a highly interesting process. ISMF allows the production of complex parts with drastically reduced costs in tooling and machinery compared to conventional processes like deep drawing. However, ISMF, with it's incremental nature, introduces the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…1b), addresses this issued by using one tool on either side of the sheet, each tool moving along a predefined tool path to deform the sheet locally, giving the sheet a desired global shape as a result of the accumulation of these local deformations (Malhotra et al [9], Meier et al [10], and Tekkaya et al [11]). Even though DSIF produces parts with better geometric accuracy than SPIF, it still does not give an accurate enough geometric compared to the desired shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1b), addresses this issued by using one tool on either side of the sheet, each tool moving along a predefined tool path to deform the sheet locally, giving the sheet a desired global shape as a result of the accumulation of these local deformations (Malhotra et al [9], Meier et al [10], and Tekkaya et al [11]). Even though DSIF produces parts with better geometric accuracy than SPIF, it still does not give an accurate enough geometric compared to the desired shape.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 Schematics of (a) SPIF (b) DSIF (c) ADSIF and (d) geometric accuracy obtained by these three approaches [11,12] ADSIF (Fig. 1c) is a new tool path strategy developed by this group [12,13], which deforms the sheet from the inner to outer circumferences without the tools moving in the Z-direction.…”
Section: Introductionmentioning
confidence: 99%
“…4 pillars: Four pillars serving as guide rails and fixture free to move vertically. 4. Scissors: Scissors design takes sheet holder down with pin in the middle.…”
Section: Fixture Design Conceptsmentioning
confidence: 99%
“…Typically a multi-axis CNC machine with a hemispherical tipped tool and sheet clamper is used for ISF [2]. Although frequently referred to as being a die-less process [3]such configurations are the exception rather than the rule [4]. More generally dies are used and ISF process can be categorized by the convexity of tooling used [ Figure 1] [5].…”
Section: ) Introductionmentioning
confidence: 99%
“…Concerning the improvement of geometrical accuracy, Tekkeya et al [28] presented a surface reconstruction algorithm to minimize geometrical deviations. Macari et al [29] suggested a few strategies to improve the accuracy including use of a flexible support, application of a counter force, backdrawing incremental forming and use of optimized trajectories.…”
Section: Introductionmentioning
confidence: 99%